Pengembangan Multimedia Interaktif dengan Aplikasi Autorun Pro Enterprise II pada Mata Kuliah Komputer Multimedia di Program Studi Teknologi Pendidikan - Nofri Hendri (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
This type of research is research development (Research and Development / R & D). This research uses Borg and Gall development model with a modified step that is (1) Doing Planning, (2) Developing the initial product, (3) Conducting product validation, (4) Conducting a limited trial and (5) Result of the final product. The product validity test is done by three validators, two media validators, and one material validator. The product test was conducted to 21 students of the FTP UNP Department of KTP who took the Multimedia Computer Courses semester July-December 2017. The instruments used were a questionnaire, assessment format, and documentation. Data were analyzed descriptively quantitative to know the quality of interactive multimedia developed. The results of the analysis show that interactive multimedia for multimedia learning, in the material aspect is in the "Good" category, for the media aspect is in the "Very Good" category. Furthermore, the results of product practicality test that has been done is in the category of "Very Good". These results show that interactive multimedia is practically used as a source of learning and alternative media in multimedia learning.